Kenya Leather Industry : Diagnosis, Strategy, and Action Plan - World Bank Group (World Bank, Washington, DC, 2015)
In 2014, Kenya’s Ministry of Industrialization requested technical assistance from the World Bank to conduct competitiveness assessments and develop competitiveness strategies for four key industries: textiles and apparel, food processing, furniture, and leather and leather products. In the context of Kenya’s long-term vision to become an industrialized middle-income country by 2030, its leather and leather products sector offers an important opportunity for industrialization and diversification of exports. The development of the sector involves improving the raw material base (especially the quality of hides and skins), boosting the tanning subsector, producing leather goods, and marketing. Key strategic questions about the leather industry include: what is the status of development of the industry, what are the most critical competitiveness challenges and opportunities, what are the most are promising leather products that Kenya should focus on moving forward, and how can support be increased to value addition and exports by upgrading production processes, technology, marketing, and branding of leather products. The basic research methodology followed a standard approach of gathering existing reports and data, and interviewing a wide range of local and international experts. To increase the competitiveness of the leather industry and accomplish the product market objectives, strategies, and actions are recommended in this report and grouped according to a framework, which consists of three key strategies: promote the dynamic restructuring of the leather industry; increase access to markets and induce greater demand for Kenyan leather and leather products; and build quality and standards.